2018
DOI: 10.1111/odi.12996
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative gingival crevicular fluid proteome in type 2 diabetes mellitus and chronic periodontitis

Abstract: Objective The aim of this study was to investigate the proteome of the gingival crevicular fluid comparing the relative abundance of proteins from type 2 diabetes mellitus (2DM) individuals and chronic periodontitis (CP) affected sites, subjects affected by both conditions and healthy individuals. Material and Methods Twenty individuals were equally allocated in four groups, 2DM with CP, 2DM periodontally healthy, CP without 2DM, and periodontally healthy without 2DM. The relative quantification of proteins wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 34 publications
1
31
0
1
Order By: Relevance
“…The investigations targeted many forms of the disease, ranging from gingivitis to mild, moderate, chronic, and aggressive periodontitis . Most studies have focused on analyses of samples from saliva, gingival crevicular fluid, and sulcular/gingival tissues …”
Section: Proteomicsmentioning
confidence: 99%
“…The investigations targeted many forms of the disease, ranging from gingivitis to mild, moderate, chronic, and aggressive periodontitis . Most studies have focused on analyses of samples from saliva, gingival crevicular fluid, and sulcular/gingival tissues …”
Section: Proteomicsmentioning
confidence: 99%
“…Vitamin D also influences the immune response through the regulation of cathelicidin [59]. Interestingly, cathelicidin is an antimicrobial peptide produced by neutrophils and has been shown that dysregulated neutrophils in periodontitis lead to a low secretion of cathelicidin [60], though this should be further investigated. Therefore, Vitamin D levels may be an interesting clinical surrogate to consider in this link of periodontitis with PD, though it demands more studies to allow strong conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…More than five decades of scientific literature have definitively demonstrated that different sampling methodologies, different sampling times and different processing protocols significantly affected both the quality and the quantity of GCF samples [94]. Up to date, only a few quantitative proteomics investigations have been performed with the aim to differentiate GCF protein profiles in periodontal health and disease [14,30,33,[38][39][40]44]. In MALDI-TOF MS, but also in other MS platforms, the ionization is influenced not only by the analyte concentration, but also by its primary structure (in fact, the presence of one or more basic residues in a peptide/protein promotes the ionization).…”
Section: Quantitation Issuesmentioning
confidence: 99%
“…Even with such limited studies, the knowledge of the biological mechanisms that can be gained from peptidomics applied both to the identification of markers of disease and to the development of therapies which has encouraged the use of in the context of progress made in this field [ 6 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. In the last decade, the impact of proteomics to the understanding of human GCF composition has progressively increased, underlining the potential diagnostic role of this fluid as invaluable source of periodontal disease-specific markers [ 6 , 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%